2009
DOI: 10.1016/j.jvs.2008.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Silent embolic infarcts on computed tomography brain scans and risk of ipsilateral hemispheric events in patients with asymptomatic internal carotid artery stenosis

Abstract: The presence of silent embolic infarcts can identify a high-risk group for ipsilateral hemispheric neurologic events and stroke and may prove useful in the management of patients with moderate asymptomatic carotid stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 34 publications
2
100
0
2
Order By: Relevance
“…In a large prospective multicenter study of 821 patients, 17% had a CT scan showing cortical, subcortical, and basal ganglia brain infarcts in patients with ≥60% asymptomatic carotid artery stenosis. In that study the cumulative strokefree rate was 0.92 (1.0% annual stroke rate) in the absence of embolic infarcts and 0.71 (3.6% annual stroke rate) in their presence (p<0.002; HR=3.0; 95%CI 1.46-6.29) 30 . The relationship between silent brain infarcts and type of plaque has also been proposed 77,78 .…”
Section: Baseline Infarcts On Ct Scan/mrimentioning
confidence: 80%
See 2 more Smart Citations
“…In a large prospective multicenter study of 821 patients, 17% had a CT scan showing cortical, subcortical, and basal ganglia brain infarcts in patients with ≥60% asymptomatic carotid artery stenosis. In that study the cumulative strokefree rate was 0.92 (1.0% annual stroke rate) in the absence of embolic infarcts and 0.71 (3.6% annual stroke rate) in their presence (p<0.002; HR=3.0; 95%CI 1.46-6.29) 30 . The relationship between silent brain infarcts and type of plaque has also been proposed 77,78 .…”
Section: Baseline Infarcts On Ct Scan/mrimentioning
confidence: 80%
“…However, only 9% of patients with ≥70% stenosis were deemed to have high risk for cerebral or retinal events based on other risk factors, such as absence of contralateral TIA or stroke, no discrete white areas (DWAs), plaque area, and GSM. In addition, Kakkos et al, analyzing data of 462 ACAD patients with 60 to 99% stenosis, showed that silent CT embolic infarcts have doubled the risk for developing a stroke compared to those without infarction 30 . Therefore, the degree of stenosis alone may no longer reflect or predict the group of patients who will have a stroke and may benefit from carotid artery intervention.…”
Section: Degree Of Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…19 A total of 146 patients were found to have ipsilateral infarcts of possible embolic origin. After a mean follow-up of 44.6 months, 102 ipsilateral ischemic events were documented (stroke in 47, TIA in 39, and amaurosis fugax in 16).…”
Section: Silent Infarcts On Ctmentioning
confidence: 99%
“…Among individuals with asymptomatic carotid stenosis, silent infarcts associate with higher risk for stroke. 7 In addition, more extensive white matter disease of the brain associates with worse outcome after stroke 8 and may be a predictor of having a stroke in general. The other major consideration in management decisions of individuals with carotid stenosis is that primary carotid endarterectomy trials were conducted in an era before routine statin use; it is likely that the same studies done in the current climate would reveal lower rates of stroke in individuals in both treatment groups as a result of the use of statins.…”
mentioning
confidence: 99%